Tai Chi and older adults health: A network science analysis of temporal changes between 1996 and 2020 - Pestana, M.H.; Sobral, M.; Wan-Chen Wang,; Artur Marecos Parreira; Luiz Moutinho (American Journal of Chinese Medicine, 2021)
Objectives: This study examines the association between older adult’s health and Tai-chi based on the past 25 years. Methods: Data was drawn from PubMed, Web-of-Science and Scopus. Patterns, trends, changes and opportunities were estimated by means of scientometric tools built on 2,202 articles, from 6,820 authors, with 26,408 citations from 3,215 institutes in 61 countries. Results: USA, China and UK are the main countries of scientific achievement, while the Harvard Medical School and Chinese University of Hong Kong are at the top of inter-institutional research collaborations. Wolf, Steven L. is the author more cited while Wayne, Peter M. is the most productive author. The hot spots are balance, mindfulness-meditation, osteoarthritis, sleep quality, cardio respiratory function, mental problems, and pain. Discussion: A network science approach allows to explore the complex structure of Tai-chi networks and to construct arguments about the development of the field. Tai-chi by involving physical movement, controlled breathing and meditation helps to maintain emotional regulation and to be self-aware, necessary for a healthy mind. Being an integral part of Chinese culture, Tai-chi as a weak implementation in the Western countries. The mental and physical benefits of Tai-chi, where time, place and practices are flexible and no special equipment is required, should make it an integral part of both cultures.